Systematic Optimize and Cost-Effective Design of a 100% Renewable Microgrid Hybrid System for Sustainable Rural Electrification in Khlong Ruea, Thailand - Montri Ngao-det; Jutturit Thongpron; Anon Namin; Nopporn Patcharaprakiti; Worrajak Muangjai; Teerasak Somsak (Energies)
This study presents a systematic approach to designing and optimizing a 100% renewable hybrid microgrid system for sustainable rural electrification in Khlong Ruea, Thailand, using HOMER Pro software (Version 3.15.3). The proposed system integrates photovoltaic (PV) panels (20 kW), pico hydro (9.42 kW), and lithium-ion battery storage (264 kWh) to provide a reliable, cost-effective, and environmentally sustainable energy solution for a remote village of 306 residents. The methodology encompasses site-specific resource assessment (solar irradiance, hydro flow), load demand analysis, and techno-economic optimization, minimizing the net present cost (NPC) and cost of energy (COE) while achieving zero emissions. Simulation results indicate the optimal configuration (S1) achieves an NPC of USD 362,687 and COE of USD 0.19/kWh, with a 100% renewable fraction, outperforming the current diesel–hydro system (NPC USD 3,400,000, COE USD 1.85/kWh, 61.4% renewable). Sensitivity analysis confirms robustness against load increases (1–5%), though battery capacity and costs rise proportionally. Compared to regional microgrids, the proposed system excels in terms of sustainability and scalability, leveraging local resources effectively. The lifecycle assessment highlights the battery’s embodied emissions (13,200–39,600 kg CO2e), underscoring the need for recycling to enhance long-term sustainability. Aligned with Thailand’s AEDP 2018–2037 and net-zero goals, this model offers a replicable framework for rural electrification in Southeast Asia. Stakeholder engagement, including community input and EGAT funding, ensures practical implementation. The study demonstrates that fully renewable microgrids are technically feasible and economically viable, providing a blueprint for sustainable energy transitions globally.